MENGUATKAN IKATAN: MEMAHAMI HUBUNGAN SUAMI ISTERI DALAM KELUARGA - Putri, Putri Amalia; Andaryuni, Lilik (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
This research aims to explore the dynamics of husband-wife relationships within Islamic family structures, focusing on both sociological and psychological perspectives. Utilizing a literature review methodology, a total of 17 scholarly articles published between 2004 and 2023 were analyzed to understand the factors influencing family relationships. The analysis techniques involved systematic selection, evaluation, and synthesis of relevant literature. The findings reveal that a harmonious husband-wife relationship is crucial for overall family well-being, highlighting the impact of emotional bonds and communication patterns. A harmonious relationship between husband and wife is identified as the key to the overall well-being of the family. Good interactions and healthy communication patterns enhance the quality of the relationship. Research has found that factors such as social pressure, individual differences, and changing times can affect the quality of the husband-wife relationship. From a sociological perspective, the husband-wife relationship is seen as part of a larger social structure. Additionally, the study provides recommendations for enhancing relationship quality in Islamic family contexts.